THE HISTOPATHOLOGICAL STUDY OF TUMOR AND TUMOR-LIKE LESIONS OF ORAL CAVITY AND OROPHARYNX - Vachhani, Anand; Bhuva, Kaushik; Patel, Harsh (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective is the histopathological study of tumor and tumor-like lesions of the oral cavity and oropharynx. Methods: This study was conducted in the Department of Pathology, SBKS Medical Institute and Research Centre, Piparia, for 1 year. One hundred oral biopsies received from the ENT department were studied. Clinical details were obtained from the requisition form. Biopsies received were processed and stained with Hematoxylin and Eosin. Histopathological diagnosis regarding type and differentiation was made. Results: Among 100 cases of the oral cavity and oropharynx biopsies analyzed in the present study, malignant lesions were 90 (90%), premalignant lesions were 4 (4%), and benign lesions were 6 (6%). The study included 86 cases (86%) of squamous cell carcinoma, 2 cases (2%) of verrucous carcinoma, 1 case (1%) of adenosquamous carcinoma, 1 case (1%) of adenocarcinoma, 3 cases (3%) of leukoplakia, 1 case (1%) of severe dysplasia, 3 cases (3%) of pleomorphic adenoma, and 1 case (1%) each of pyogenic granuloma, squamous papilloma, ossifying fibroma. Maximum number of cases was of squamous cell carcinoma (86%). Maximum number of cases was seen inthe age group of 36–45 years, the youngest patient was 25 years old. There was a male preponderance for oral and oropharyngeal lesions (73%) as compared to females (27%). Male: Female ratio was 1:0.37. The most common site of the lesion was the tongue (41%) followed by buccal mucosa (30%). The majority of the tumors were well-differentiated. Conclusion: Males are more likely to develop lesions of the oral cavity and oropharynx than females. Typically, older age groups are affected. Drinking alcohol, smoking, and chewing tobacco can contribute to oral and oropharyngeal lesions. The most frequent place implicated is the tongue. The most prevalent histological variation is squamous cell carcinoma, and the majority of these tumors are well-differentiated.